Therapeutic potentialities of green tea (Camellia sinensis) and aloe vera (Aloe barbadensis) on Staphylococcus aureus induced septic wound in goats - Tamanna, Sumaia Jahan; Shihab, Moktadin Md.; Akter, Mst Antora; Rahman, Marzia; Alam, Md Mahmudul (Journal of the Bangladesh Agricultural University, 2020)
The research has been conducted in Black Bengal goats to determine the therapeutic efficacy of aloe vera and green tea extract on the healing of Staphylococcus aureus induced septic wound. A total 18 surgical wounds were made in goats under three groups; aqueous paste of aloe vera (Group-A), alcoholic extract of green tea (Group-B) and normal saline (as control, Group-C). Each wound was 20 mm length and 5 mm depth. Wound was remained open and 0.5 ml medium (107 /ml) containing Staphylococcus aureus was inoculated in each wound. After 72 hours of bacterial inoculation treatment was started. Freshly prepared aloe vera paste and alcoholic extract of green tea was applied once daily onto the wound in group A and B respectively. Similar action was taken in Group-C with normal saline only. Follow up information was recorded from day 0 to day 21 postoperatively. Some morphological characters such as swelling, wound gap and length of wound were observed. Highest wound gap (5.18 ± 0.32 mm) was observed in wounds of control animals where it was lowest (4.63 ± 0.14 mm) in those treated with extract of green tea. Length of wound was also highest (13.74 ± 0.38 mm) in control group and lowest (12.62 ± 0.17 mm) in green tea treated group. All wounds were regularly monitored to observe the complications like swelling, edema, wound dehiscence, wound abscess, local infection and exudation surrounding the wounds. Mean days to heal completely were 15 days for aloe vera, 13 days for green tea and in control group it took 20 days to achieve similar results. Bacteriological studies revealed presence of higher bacterial load in the control group than the other two groups which is responsible for delayed healing. Our results showed that Staphylococcus aureus induced wound healing was prompted by the topical use of both green tea and aloe vera but green tea extract was more effective than aloe vera. Therefore, it can be suggested that alcoholic extract of green tea and aqueous extract of aloe vera could be good alternative to antibiotic for the treatment of Staphylococcal wound in goat. J Bangladesh Agril Univ 18(1): 105–110, 2020 https://doi.org/10.5455/JBAU.94746